Improving conductivity of rotary screen printed microparticle silver conductors using a roll-to-roll calendering process - Jansson, Elina; Hast, Jukka; Petäjä, Jarno; Honkala, Jorma; Häkkinen, Juha; Huttunen, Olli-Heikki (Journal of Print and Media Technology Research, 2023)
A roll-to-roll (R2R) calendering process was developed and used to improve the conductivity of rotary screen printed microparticle silver conductors. Two commercial microparticle silver pastes were used. In the calendering process, the rotary screen printed microparticle silver conductors are compressed under pressure and heat in order to make the porous microparticle layer denser and flatter. The results show that the resistivity of the rotary screen printed microparticle silver conductors was dramatically dropped after the R2R calendering process by 29–56 % depending on the silver paste. The complete drying of the calendered conductor layer decreased the resistivity even further as a result of which the layer resistivity was decreased 74 % from its initial value. The roughness of the silver conductors was also reduced remarkably after the calendering by 45–72 %. The effect of the R2R calendering process on the printed inductively remote readable capacitive moisture sensor based on simple inductor-conductor resonant circuit was also demonstrated. Calendering improved the Q-factor of the sensor but decreased the resonance frequency.